Application of wavelet-matched filters to holographic associative memories - Widjaja, Joewono; Tomita, Yasuo; Abdul Rahman, Abdul Wahab (Elsevier, 1996)
We propose a novel method for improving association abilities of a holographic associative memory by using wavelet-matched filtering. Based on an edge-enhancement and muitiscaling properties of the wavelet transform, a sharp correlation peak between a partial input and a stored datum can be obtained. This leads to higher association abilities. Autoand hetero-association operations are demonstrated experimentally.